2021
DOI: 10.1021/jacsau.1c00212
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Site Isolation: Keys to High Propane Dehydrogenation Performance of Silica-Supported PtGa Nanoparticles

Abstract: Nonoxidative dehydrogenation of light alkanes has seen a renewed interest in recent years. While PtGa systems appear among the most efficient catalyst for this reaction and are now implemented in production plants, the origin of the high catalytic performance in terms of activity, selectivity, and stability in PtGa-based catalysts is largely unknown. Here we use molecular modeling at the DFT level on three different models: (i) periodic surfaces, (ii) clusters using static calculations, and (iii) realistic siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 114 publications
(222 reference statements)
0
52
0
Order By: Relevance
“…Without Sn, the propene can readily further dehydrogenate to form the deep dehydrogenation products. The presence of Sn donates electron to Pt and helps to reduce the propene adsorption and dehydrogenation on Pt sites, which can also be realized by other metal dopants (e.g., Ga, Zn) 16 , 31 , 32 . Recently, Linic et al 6 also reported a silica-supported PtSn nanoparticles with excellent PDH activity, in which they initially introduce a heterometallic Pt-Sn coordination complex with intimate Pt and Sn contact.…”
Section: Resultsmentioning
confidence: 99%
“…Without Sn, the propene can readily further dehydrogenate to form the deep dehydrogenation products. The presence of Sn donates electron to Pt and helps to reduce the propene adsorption and dehydrogenation on Pt sites, which can also be realized by other metal dopants (e.g., Ga, Zn) 16 , 31 , 32 . Recently, Linic et al 6 also reported a silica-supported PtSn nanoparticles with excellent PDH activity, in which they initially introduce a heterometallic Pt-Sn coordination complex with intimate Pt and Sn contact.…”
Section: Resultsmentioning
confidence: 99%
“…As recently demonstrated by MTD calculations for a SOMC derived PtGa system, a strong effect of the support on the nanoparticle structure can be expected. 35 We thus investigated the role of the oxide support by building a more complex model placing the coreshell Pt2Mn particle -identified as the energetic ground state in the preceding calculation in vacuum -at the surface of an amorphous dehydroxylated silica support 49 bearing 5 Mn II sites (see supporting information for details on the construction of this oxide model). Along the simulation, the Mn-O MTD coordination number increases steadily at the expense of the Mn-Mn and Mn-Pt coordination numbers, which tend to decrease along the simulation, suggesting a strong affinity of Mn 0 for the oxide support (Figure 3, C)-right & Figure S54).…”
Section: (See Supporting Information Figures S18 and S19 For Detail)mentioning
confidence: 99%
“…SiO2 is thus ideally suited to study structure-property relationships of surface species, avoiding interference from the support. This SOMC/TMP approach combined with detailed spectroscopic -including X-ray absorption spectroscopy (XAS), X-ray photoelectron spectroscopy (XPS) and infrared spectroscopy (IR) -and computational studies -using in particular metadynamics (MTD) at the DFT level 35 -has enabled the development of PtGa-based PDH catalysts with high catalytic performances. Such analysis helped to derive structure-performance relationships, tracing back the catalytic performance to i) Pt site isolation at the nanoparticle surface and ii) increased dynamics of Pt sites in the alloyed nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 However, the role of platinum in PtGa catalysts is currently debated, ranging from a promoter of coordinately unsaturated Ga 3+ active sites, 4 to the active phase itself, such as site-isolated Pt atoms in metallic PtGa alloyed nanoparticles. 5 …”
Section: Introductionmentioning
confidence: 99%